Research on Low-Flammable Textile and Building Materials (Eurasian Journal of Research, Development and Innovation, 2023)
This article presents a study of fire retardant AC and ABS obtained on the basis of orthophosphoric acid and vermiculite in the form of a suspension. The proposed suspension increases the flammability and reduces smoke formation of building and textile materials.